2011
DOI: 10.1021/ol202528k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Benzomacrolactone-Based Somatostatin Mimetic

Abstract: The benzomacrolactone is a framework found in numerous natural products. The synthesis of an orthogonally functionalized benzomacrolactone from D-glucosamine and a salicylic acid derivative is described. This macrolactone was used for the synthesis of a somatostatin mimetic that has submicromolar affinity for the human somatostatin receptor 4 (hSSTR4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Indeed, 3 a is easily converted in three straightforward steps into the corresponding aryl ε‐lactam 11 (78 % overall yield in three steps), via the amino aryl ester 12 , which provides the basis for an efficient route to bioactive compounds such as a ghrelin receptor antagonist, a putative antiobesity pharmaceutical,12g and aspartyl protease inhibitors for the treatment of Alzheimer’s disease12d (Scheme ). The aldehyde 3 a can also be converted in two steps into the hydroxyaryl acid 14 , which represents the basic skeleton for somatostatin mimetics,12f and into the aryl ε‐lacton 13 . Thus, the obtained products represent important building blocks in the synthesis of several classes of aforementioned valuable compounds 12…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, 3 a is easily converted in three straightforward steps into the corresponding aryl ε‐lactam 11 (78 % overall yield in three steps), via the amino aryl ester 12 , which provides the basis for an efficient route to bioactive compounds such as a ghrelin receptor antagonist, a putative antiobesity pharmaceutical,12g and aspartyl protease inhibitors for the treatment of Alzheimer’s disease12d (Scheme ). The aldehyde 3 a can also be converted in two steps into the hydroxyaryl acid 14 , which represents the basic skeleton for somatostatin mimetics,12f and into the aryl ε‐lacton 13 . Thus, the obtained products represent important building blocks in the synthesis of several classes of aforementioned valuable compounds 12…”
Section: Methodsmentioning
confidence: 99%
“…Compounds designed to target SSTRs. Syntheses of some compounds used in this study has been reported earlier (see Figure 2) and these include the iminosugars [30][31][32][33], benzomacrolactones [34] and pyranoside 3 originally designed by Hirschmann and co-workers [35]. New compounds based on the pyranose ManNAc, the Eannaphane macrocycle, as well as acyclic/cyclic peptidyl scaffolds are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we found that attempts to carry out a Gabriel reaction with PhthK were unsuccessful and led to decomposition. However, the use of Boc2NK gave the useful intermediate 27 (Scheme 1) [34].…”
Section: Synthesis Of Somatostatin Mimetics Based On 2-deoxy-2-acetamido-d-mannopyranosementioning
confidence: 99%
“…More successful results were obtained in the nickel-catalysed reductive cyclization of ynals 137 to macrocyclic allylic alcohols with 14-to 22-membered rings (Scheme 11.17). 242 This reaction can provide both endocyclic (138) and exocyclic (139) alkenes depending upon the ligand employed, the nature of the alkyne (terminal or internal) and the reducing agent. The optimized process has been subsequently applied to the preparation of modified macrolide structures.…”
Section: Nickel-mediated Reactionsmentioning
confidence: 99%